Chapter 2: Patient Care Process (Foundations in Clinical Pharmacy Practice, 2025)
AuthorMr. Vijay Anand Kada, PharmD Scholar, Department of Pharmacy Practice, Pydah College of Pharmacy, Kakinada, Patavala, Andhra Pradesh, IndiaAbstractThe systematic patient care process provides a comprehensive framework for delivering clinical pharmacy services through five interconnected steps. Assessment techniques encompass medication history collection, laboratory data interpretation, and symptom evaluation to identify medication-related problems. Care planning involves prioritizing identified problems, establishing measurable outcomes, and developing patient-specific interventions considering efficacy, safety, and feasibility. Implementation strategies include direct interventions, prescriber recommendations, patient education, and care coordination. Monitoring evaluates therapy effectiveness, adverse effects, and adherence through appropriate parameter selection and follow-up scheduling. Documentation using standardized formats captures clinical reasoning, interventions, and outcomes through problem-oriented approaches, SOAP notes, and care plans. This standardized process ensures comprehensive pharmaceutical care delivery, facilitates communication with healthcare teams, demonstrates value, and improves patient outcomes through systematic medication management addressing both actual and potential drug therapy problems.Keywords: Pharmaceutical Care Plan, Medication Therapy Management, Drug Therapy Problems, Patient Monitoring, Clinical DocumentationVIEW PDF